Sankcioniranje kršitev prava varstva potrošnikov - Weingerl, Petra (Pravni letopis, 2023)
The mere existence of consumer rights is not enough for the proper functioning of the market, as it is crucial that they are also enforced in practice. The purpose of the contribution is to present the legal framework, which is intended to sanction breaches of the rules of consumer protection law, with an emphasis on ZVPot-1. The rules on sanctioning breaches of consumer legislation are extremely complex. ZVPot-1 regulates sanctions from three branches of law - administrative, criminal, and civil. Both public law and civil law rules (i.e. public and private enforcement) pursue the same goal: a deterrent effect on the trader. This contribution focuses on administrative and criminal enforcement and on private enforcement only in the context of novelties in the field of unfair business practices.
Keywords: civilnopravno varstvo; Evropska unija; javnopravno varstvo; kaznovalno varstvo; potrošniško pravo; pravice potrošnikov; pravo varstva potrošnikov